Liquid Biopsy perspectives theranostics and personalized oncology - C Daniel Ascencio González (Annals of Cytology and Pathology - Peertechz Publications, 2020)
The current limitations of cancer diagnosis and molecular profiling based on invasive tissue biopsies or clinical imaging have led to the development of the Liquid Biopsy field (LB), includes the isolation of Circulating Tumor Cells (CTCs), circulating free or tumor DNA (cfDNA or ctDNA), Extracellular Vesicles (EVs), and Tumor-Educated Platelets (TEPs) from body fluid samples and their molecular characterization to identify biomarkers for early cancer diagnosis, prognosis, therapeutic prediction, and follow-up. As cancers grow, evolve, and spread, they shed circulating tumor cells (CTCs), as well as other tumor-associated cells and products, into the bloodstream. Capturing and analyzing CTCs or other tumor-associated cells and products from a patient's blood sample can provide insight into particular cancer's biology, response to treatment, and/ or potential therapeutic targets. CTCs are heterogeneous; a pressing question concerns which CTCs represent those directly involved in metastasis, the major cause of cancer-related death. The aim of this review, is to describe the biological principles underlying the Liquid Biopsy (LB) concept and to discuss how functional studies can expand the clinical applications of these circulating biomarkers.